The ‘Art World’ of the Auction Houses: The Role of Professional Experts - Neil Brodie (Arts, 2019)
Auction sales of unprovenanced, likely stolen, cultural objects continue to generate controversy. But while auction houses can appear to be relatively passive agents in the sales process, providing a platform for bringing together buyers and sellers, in reality their business practices are more complex. With reference to three recent disputed auctions of cultural objects, this paper explores in more detail the ‘art world’ of auction house business practices, exploring in particular the central role of professional experts in supporting auction sales and the legal and ethical implications of their involvement.